Finite Element Analysis Of Reasonable Foundation For Supporting Silo’s Tower - Nurdin, Sukiman (Jurusan Teknik Sipil Universitas Tadulako, 2012)
The limitation of soil data due to poor soil investigation process is a common problem in civil engineering project. The finite element method was used to analyse the compatibility of foundation to support silos in Liverpool Docks. Both shallow foundation and pile foundation were considered. The results of the analyses are presented by comparing analytical and numerical solution. Parametric study was considered for each case. There are different results for two types of shallow foundation that had been considered. Strip foundation seemed more reliable than pad foundation, while Pile foundation considered to be first choice due to the satisfactory condition for all factors